CLIMATIC CHANGE AND HUMAN IMPACT - Gkamplias, Panagiotis; Dimitropoulos, Timos; Tolias, Nikolas; Markopoulos, Giorgos (Open Schools Journal for Open Science, 2025)
Climate change is a long-term alteration of temperature and typical weather patterns in a place. While climate fluctuations have occurred throughout Earth’s history, the current pace and scale of change are unprecedented. Human activities, especially the burning of fossil fuels and deforestation, are significantly contributing to the greenhouse effect, resulting in global warming and widespread environmental consequences. This document explores the underlying causes of climate change, its devastating effects on both ecosystems and human societies, and potential solutions to mitigate its impact. The purpose is to foster greater awareness and encourage responsible environmental behavior at all levels of society.